Understanding the pathophysiological mechanisms of cardiometabolic complications in obstructive sleep apnoea: towards personalised treatment approaches. Issue 2 (6th August 2020) - Ryan, Silke; Cummins, Eoin P.; Farre, Ramon; Gileles-Hillel, Alex; Jun, Jonathan C.; Oster, Henrik; Pepin, Jean-Louis; Ray, David W.; Reutrakul, Sirimon; Sanchez-de-la-Torre, Manuel; Tamisier, Renaud; Almendros, Isaac
In January 2019, a European Respiratory Society research seminar entitled "Targeting the detrimental effects of sleep disturbances and disorders" was held in Dublin, Ireland. It provided the opportunity to critically review the current evidence of pathophysiological responses of sleep disturbances, such as sleep deprivation, sleep fragmentation or circadian misalignment and of abnormalities in physiological gases such as oxygen and carbon dioxide, which occur frequently in respiratory conditions during sleep. A specific emphasis of the seminar was placed on the evaluation of the current state of knowledge of the pathophysiology of cardiovascular and metabolic diseases in obstructive sleep apnoea (OSA). Identification of the detailed mechanisms of these processes is of major importance to the field and this seminar offered an ideal platform to exchange knowledge, and to discuss pitfalls of current models and the design of future collaborative studies. In addition, we debated the limitations of current treatment strategies for cardiometabolic complications in OSA and discussed potentially valuable alternative approaches. The pathogenesis of cardiometabolic complications in obstructive sleep apnoea is poorly understood and this perspective summarises the key learning points of an ERS research seminar discussing the interaction of potential pathophysiological triggers http://bit.ly/2vANqBi